Comparison between rosuvastatin and atorvastatin for the prevention of contrast-induced nephropathy in patients with STEMI undergoing primary percutaneous coronary intervention - Ata Firouzi; Ali Kazem Moussavi; Ahmad Mohebbi; Mohammad Javad Alemzadeh-Ansari; Reza Kiani; Hamid Reza Sanati; Bahram Mohebbi; Farshad Shakerian; Ali Zahedmehr; Mohammad Mostafa Ansari-Ramandi; Saeed Oni Heris; Bahar Ghaleshi; et al. (Journal of Cardiovascular and Thoracic Research, 2018)
Introduction: There is some controversy over the efficacy of statins for the prevention of contrastinduced nephropathy (CIN). There have also been reports on varying efficacies of different statins. Hence, in this study the efficacy of atorvastatin and rosuvastatin for the prevention of CIN was assessed. Methods: This single-blind randomized clinical trial was performed on 495 random patients with myocardial infarction with ST-segment elevation undergoing primary percutaneous coronary intervention (PCI) in a training referral hospital in 2015. Patients were randomly assigned to receive either atorvastatin 80 mg at admission and daily or rosuvastatin 40 mg at admission and daily. CIN was defined based on serum creatinine elevation after 48 hours from the PCI. Results: The incidence of CIN was observed in 63 patients (21.4%) After 48 hours from primary PCI. Of those, 17% (n = 50) were grade 1 CIN, while 4.4% (n = 13) were grade 2 CIN. There was no significant difference between rosuvastatin group compared with atorvastatin group, regarding the CIN grading (P = 0.14). Conclusion: Our results indicate that atorvastatin and rosuvastatin have similar efficacy for the prevention of CIN.